Microbiome engineering to enhance disease resistance in aquaculture: current strategies and future directions - Tayyab, Muhammad; Zhao, Yongzhen; Zhang, Yueling (Frontiers in Microbiology, 2025)
Aquaculture, a cornerstone of global food security, faces critical threats from disease outbreaks, antimicrobial resistance, and ecological disruption. Through a narrative analysis of over 160 studies, this review synthesizes advances in microbiome engineering—a sustainable approach to enhancing disease resistance in aquatic animals—addressing key gaps: the inconsistent efficacy of conventional probiotics and prebiotics under field conditions, and the need for climate-resilient solutions. Critically, we highlight the emergence of precision microbiome engineering as a transformative paradigm. We integrate findings from genomics, metabolomics, clustered regularly interspaced short palindromic repeats, and artificial intelligence to identify microbial strategies that enhance host resilience. Genomic and multi-omics methods reveal health-associated microbes and metabolites, such as Vibrio-dominated dysbiosis markers in shrimp and butyrate-mediated immunity. Guided by these biomarkers, we describe precision-tailored probiotics—host-derived or genome-edited Bacillus subtilis strains whose adhesion factors, metabolic outputs (e.g., butyrate, bacteriocins), and heat stress tolerance are matched to the target species’ gut niche. These are combined with complementary prebiotics (e.g., chitosan oligosaccharides) and synbiotics (e.g., Lactiplantibacillus plantarum plus king oyster mushroom extracts) that suppress pathogens through competitive exclusion and immune modulation. Ecologically rational innovations—interventions explicitly grounded in ecological theory (niche complementarity, K-selection) to stabilize resource-efficient microbiomes—such as fecal microbiota transplantation and synthetic consortia, demonstrate further disease control potential. Our synthesis reveals that translating microbiome engineering from laboratory to farm requires overcoming host-microbiome compatibility challenges and ecological risks. Policy alignment with the United Nations Sustainable Development Goals—Zero Hunger (Sustainable Development Goal 2), Climate Action (Sustainable Development Goal 13), and Life Below Water (Sustainable Development Goal 14)—is critical for sustainable adoption.